Design and validation of a food frequency questionnaire to assess diet among Yaqui Indians from Sonora, México - Serna Gutiérrez, Araceli; Esparza-Romero, Julian (Acta Universitaria, 2019)
The Yaquis have a high prevalence of obesity and information about their diet is limited. The objective was to design and validate a food consumption frequency questionnaire to evaluate the diet of Yaqui adults (FFQY). The FFQY design derived from the application of two 24 h recalls (24hR) in 156 Yaquis. The validation of FFQY vs. 24hR for total energy, macronutrients and micronutrients was performed by Pearson correlation (r), intraclass correlation (IC) and Bland and Altman (BA) graph. The FFQY included 123 foods, three serving sizes and five consumption frequency categories. The coefficients of r were between 0.23 and 0.56, indicating acceptable and good correlations. The IC coefficients were higher than those of Pearson, and the BA graph showed higher values for the FFQY vs. 24hR. The FFQY is a feasible tool to study the diet of Yaqui adults.